MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMKN 3 SELAT PANJANG - Ramli, Ramli; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, purpose of this study was to determine the motivation of students in physical education sport and health in SMK 3 Selat Panjang. This type of research is Deskriptive. The population in this study were all students of SMK 3 Selat Panjang, amounting to as many as 428 people. Samples were taken by random sampling technique, thus the number of samples is as many as 38 people. The type of data in the study of primary data, data collected by the researchers to propose a questionnaire to students. While the secondary data, the data retrieved from the archive documentation Administration students from the School. Furthermore, the data were analyzed by using a percentage score of ideal values. Based on the analysis of data shows that intrinsic motivation Intrinsic motivation veriabel students at SMK 3 Selat Panjang obtained level of achievement of 84.70%, were classified as